The Protective Impacts of α-tocopherol Supplementation on the Semen Quality of Sapera Goat Preserved at 4⁰C - R. A. Prastiya; Rimayanti; M. M. Munir; A. P. Nugroho (Faculty of Animal Science, Bogor Agricultural University, 2021)
Supplementation of vitamin E (α-tocopherol) as an antioxidant into an extender is useful to maintain sperm quality during the process of cryopreservation by protecting the sperms from reactive oxygen species (ROS). This study aims to evaluate the protective impacts of vitamin E supplementation on the motility, viability, and reducing the abnormality of sperms in Sapera goats. The sample of semen used in the present study was obtained from fresh semen and good-quality ejaculates of the Sapera goats collected by an artificial vagina. The groups involve one controlled treatment group, which contains semen and tris egg yolk (TEY) extender without vitamin E (P0), and three treatment groups that contain semen, TEY extender, and different doses of vitamin E, i.e., 1 mg/mL (P1), 2 mg/mL (P2), and 3 mg/mL (P3), respectively. Data obtained from the experiments were analyzed using Repeated Measures Multivariate Analysis (MANOVA). The results showed that TEY extenders added with vitamin E at a dose of 1 mg/mL of vitamin E (P1) produced the highest motility and viability with the lowest abnormalities of sperm after 24th hour of cryopreservation. The lowest sperm motility and viability among the treatment groups was observed in the TEY extender added with vitamin E at a dose of 3 mg/mL (P3) at 96th hour after cryopreservation, which was almost the same as the control group without vitamin E (P0) that had the lowest motility and viability. In conclusion, the current study found that supplementation of vitamin E as an antioxidant at a dose of 1 mg/mL in TEY extender can preserve semen of the Sapera goats in refrigerator up to 96 h at 4°C and provides higher sperm motility and viability percentage, with a lower percentage of sperm abnormality.